2020
DOI: 10.1515/math-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

A new blow-up criterion for the Nabc family of Camassa-Holm type equation with both dissipation and dispersion

Abstract: Abstract In this paper, we investigate the Cauchy problem for the Nabc family of Camassa-Holm type equation with both dissipation and dispersion. Furthermore, we establish the blow-up result of the positive solutions in finite time under certain conditions on the initial datum. This result complements the early one in the literature, such as [E. Novruzov, Blow-up phenomena for the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…en, the propagation speed with compact supported initial datum was investigated, which improves early results [40][41][42]. On the other hand, the authors [39] constructed blowup threshold for a positive solution in finite time under certain condition of initial datum, that complements early works [36,37]. Now, we introduce the structure of equation ( 1).…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…en, the propagation speed with compact supported initial datum was investigated, which improves early results [40][41][42]. On the other hand, the authors [39] constructed blowup threshold for a positive solution in finite time under certain condition of initial datum, that complements early works [36,37]. Now, we introduce the structure of equation ( 1).…”
Section: Introductionmentioning
confidence: 52%
“…Lately, the authors discussed the blowup rate of the wave-breaking solution, which complement the result of [37]. Except D-G-H equation, Zhang [38,39] also studied the Cauchy problem for the N − abc family of the C-H type equation with dispersion and dissipation…”
Section: Introductionmentioning
confidence: 94%
“…In this section, we turn to our attention to establish a semi-linear system for smooth solutions. For that purpose, it is crucial to introduce the characteristic equation [55,56]…”
Section: Semi-linear System For Smooth Solutionsmentioning
confidence: 99%
“…where N ∈ Z + , N ≥ 1, a, b, c are positive constants and a = b + c. More details are present in [55,56].…”
Section: Introductionmentioning
confidence: 99%
“…e long-time behavior for the support of momentum density of the Camassa-Holm equation was discussed in [25]. Mathematical studies for the related models can been found in [26][27][28].…”
Section: Introductionmentioning
confidence: 99%